Dietary omega-3 fatty acids and fish consumption and risk of type 2 diabetes - Djoussé, Luc; Gaziano, J Michael; Buring, Julie E; Lee, I-Min (The American journal of clinical nutrition, 2011)
Although dietary omega-3 (n-3) fatty acids may confer some cardiovascular benefits, it is unclear whether these nutrients may also unfavorably affect risk of type 2 diabetes (T2D). We evaluated whether dietary omega-3 fatty acids and fish consumption were associated with increased risk of T2D. This was a prospective study of 36,328 women (mean age: 54.6 y) who participated in the Women's Health Study and who were followed from 1992 to 2008. Incident T2D was self-reported and validated primarily through the collection of supplementary information from participants. Information on omega-3 and fish intakes was obtained by using a validated food-frequency questionnaire. We used Cox proportional hazard models to estimate adjusted relative risks. During an average follow-up of 12.4 y, 2370 women developed T2D. Marine but not plant-based omega-3 fatty acids were positively associated with incident T2D. From the lowest to highest quintiles of marine omega-3 intake, the multivariable-adjusted hazard ratios (95% CIs) for T2D were 1.0 (referent), 1.17 (1.03, 1.33), 1.20 (1.05, 1.38), 1.46 (1.28, 1.66), and 1.44 (1.25, 1.65), respectively (P for trend < 0.0001). A similar association was observed with fish intake, but additional adjustment for docosahexaenoic acid led to the elimination of the association. The relation between marine omega-3 fatty acids and T2D was observed in hypertensive and nonhypertensive subjects and in women who reported infrequent fish consumption. Our data suggest an increased risk of T2D with the intake of long-chain omega-3 fatty acids, especially with higher intakes (≥ 0.20 g omega-3/d or ≥ 2 servings of fish/d). The Women's Health Study was registered at clinicaltrials.gov as NCT00000479.